The Potential for Circulating Tumor Cells in Pancreatic Cancer Management - Pimienta, Michael; Edderkaoui, Mouad; Wang, Ruoxiang; Pandol, Stephen (Frontiers in Physiology, 2017)
Pancreatic cancer is one the most lethal malignancies. Only a small proportion of patients with this disease benefit from surgery. Chemotherapy provides only a transient benefit. Though much effort has gone into finding new ways for early diagnosis and treatment, average patient survival has only been improved in the order of months. Circulating tumor cells (CTCs) are shed from primary tumors, including pre-malignant phases. These cells possess information about the genomic characteristics of their tumor source in situ, and their detection and characterization holds potential in early cancer diagnosis, prognosis, and treatment. Liquid Biopsies present an alternative to tumor biopsy that are hard to sample. Below we summarize current methods of CTC detection, the current literature on CTCs in pancreatic cancer, and future perspectives.